1984
DOI: 10.1128/aac.25.5.575
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance percentage as a criterion for the detection of tolerant Staphylococcus aureus strains

Abstract: In this study, the degree of tolerance was determined in several populations of Staphylococcus aureus isolates. The degree of tolerance of a staphylococcal strain can be established in a reproducible way by exposing the strain to increasing concentrations of a ,-lactam antibiotic and determining the number of surviving bacteria at each concentration. The The efficacy of antimicrobial treatment in infections caused by staphylococci with a high MBC:MIC ratio was studied several times. A negative correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…The differences in bacterial survival of tolerant and nontolerant strains in the thighs of mice treated with methicillin support the view that, in some cases, the results of treatment of staphylococcal infections depend not only on the MIC value of the causative agent but also on the killing rate (4).…”
Section: Methodssupporting
confidence: 55%
“…The differences in bacterial survival of tolerant and nontolerant strains in the thighs of mice treated with methicillin support the view that, in some cases, the results of treatment of staphylococcal infections depend not only on the MIC value of the causative agent but also on the killing rate (4).…”
Section: Methodssupporting
confidence: 55%
“…Bradley et al (5) found that 16 of 30 strains were tolerant to oxacillin and cephalothin with 0.2 to 43% of the initial log 5-cfu/ml stationary-phase inoculum surviving after 24 h of incubation in Mueller-Hinton broth. Goessens et al (13) obtained similar results for 64 isolates, with 12.5% of the isolates showing more than 2% survivors after 24 h of incubation for a variety of antimicrobial concentrations, and termed this the tolerance percentage. Several retrospective clinical studies have suggested that the clinical response to beta-lactam therapy of antimicrobial agent-tolerant infections might be impaired (8,17,30), but tolerance did not affect the response to treatment in the rabbit model of staphylococcal endocarditis (14) or the rat model of staphylococcal pyelonephritis (16).…”
supporting
confidence: 60%
“…Clear tubes were sampled after 24 h of incubation at 35°C with a calibrated 0.01-ml loop and streaked on quadrants of a sheep blood agar plate. CFUs were counted after 18 to 24 h of incubation at 35°C, and the MBC was read as the lowest antibiotic (13,25,33,37), with cross tolerance for methicillin, oxacillin, cephalothin, penicillin G, and vancomycin but not gentamicin (25). Killing was increased by 48 h of incubation as compared with 24 h of incubation for methicillin, oxacillin, penicillin G, cephalothin, vancomycin, and gentamicin.…”
mentioning
confidence: 99%
“…ADPC MIC plate counts fell dramatically at the MIC and were essentially absent on plates with concentrations above the MIC as long as oxacillin action was permitted to continue. ADPC MBC plate-count patterns showed significantly less variation and inoculum phase (5,18,20,21,25,29), incubation time (1,19,22,26,34,36), and carry-over of antimicrobial agents from MIC tubes to MBC plates (12,19,31,33) have been shown to influence the measured incidence of tolerance and related phenomena for a variety of bacteria and antimicrobial agents. Less intuitively obvious has been the finding that bacteria subjected to broth dilution procedures may be inadvertently protected from the action of antimicrobial agents in broth cultures, thus causing tolerance interpretations to be spuriously high and often irregular in manifestation and reproducibility (15,26,39).…”
Section: Methodsmentioning
confidence: 99%
“…Goessens and associates (10,11,12), using a carefully controlled BDPC method, recently introduced tolerance percentage to indicate the percentage of CFU surviving antimicrobial action. They found tolerance percentage to be strain dependent for S. aureus versus oxacillin and arbitrarily defined tolerance as a tolerance percentage of 2% or greater.…”
Section: Methodsmentioning
confidence: 99%